L2 Vocabulary Acquisition: Investigating the Key to Lexical Comprehension - Giridharan, Beena; Conlan, C. (2016)
L2 researchers have debated the significance of the lexicon in addition to the relevance of acquiring syntax, in the learning of an L2. (Huckin et.al, 1993; Haastrup, 1991) and other researchers in the field of SLA recognize the fact that learners’ knowledge of words from context assists them in the comprehension of unfamiliar words that they encounter in their reading materials. Academic reading materials tend to be cognitively demanding and often require language in which contextual cues for meaning are reduced. Research in lexical acquisition has gained significant grounds lately, comparable to that of studies in the acquisition of syntax, which have played a prominent role in SLA.